Remote activities of cognitive stimulation for older adults during the COVID-19 pandemic: a systematic review - Etiene Souza Madeira; Priscilla Alfradique de Souza; Anderson Amaral (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: Cognitive stimulation activities for older adults are generally carried out in face-to-face workshops. However, during the COVID-19 pandemic, these activities and consultations became remote due to social isolation, enabling care to continue safely. This study aims to analyze the remote cognitive stimulation and/or telerehabilitation activities for older people that were carried out as an intervention during the COVID-19 pandemic. This is a systematic review study with five selected articles, conducted according to the PRISMA statement methodology. Among the main results, the feasibility and acceptance of remote cognitive stimulation activities using technologies during the pandemic stand out, reflecting on future and expanded use for different realities and cultures. the studies reviewed also indicate the stabilization and improvement of the cognitive state and of depressive and anxious feelings, as well as the maintenance of independence of these participants, with an increase in scores on scales applied before and after the interventions. In conclusion, the activities carried out in cognitive stimulation and/or telerehabilitation therapies for older adults as an intervention during the COVID-19 pandemic had an average of 47 participants; the technologies used for the activities were tablet and personal computer; pre-installed programs were the most used strategy; and the interventions lasted from 1 to 3 months, with activities 2 to 3 times per week. The reinvention of techniques aimed at stimulating and rehabilitating the cognitive health of the older adults, via technologies as a strategy to replace or complement face-to-face activities, promotes the cognitive and mental health and independence of the older population.